2022
DOI: 10.1002/rcr2.995
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of acute respiratory failure following SARS‐CoV‐2 vaccination in post‐COVID‐19 pneumonia

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination is a very effective method of preventing infection and is recommended for people having recovered from coronavirus disease 2019 . In this novel case report, we describe two patients with post-COVID-19 pneumonia who experienced acute respiratory failure and new bilateral ground-glass opacities several days after receiving SARS-CoV-2 vaccination. Both patients were treated with methylprednisolone pulse therapy and recovered from the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The third type, a recombinant new coronavirus vaccine [Chinese hamster ovary (CHO) cells, which are stably expressing SARS-CoV-2 spike protein], is produced by Zifivax using a protein to trigger an immune response ( 18 ). PiCoVacc9 and BBIBP-CorV10 are widely used, eliciting neutralizing antibodies (NAbs) in mice, rats, and non-human primates, with the nonhuman primates in the high-dose group being fully protected from infection by SARS-CoV-2 with no antibody-dependent enhancement (ADE) ( 18 , 32 ), while ADE has been observed in clinical cases ( 33 , 34 ). Evaluations of COVID-19 vaccine safety and efficacy have shown that vaccination can yield excellent efficacy against the original strain and some variants, while the risk of adverse events is acceptable ( 19 , 35 - 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…The third type, a recombinant new coronavirus vaccine [Chinese hamster ovary (CHO) cells, which are stably expressing SARS-CoV-2 spike protein], is produced by Zifivax using a protein to trigger an immune response ( 18 ). PiCoVacc9 and BBIBP-CorV10 are widely used, eliciting neutralizing antibodies (NAbs) in mice, rats, and non-human primates, with the nonhuman primates in the high-dose group being fully protected from infection by SARS-CoV-2 with no antibody-dependent enhancement (ADE) ( 18 , 32 ), while ADE has been observed in clinical cases ( 33 , 34 ). Evaluations of COVID-19 vaccine safety and efficacy have shown that vaccination can yield excellent efficacy against the original strain and some variants, while the risk of adverse events is acceptable ( 19 , 35 - 37 ).…”
Section: Introductionmentioning
confidence: 99%